Mechanisms Underlying Serotonergic Excitation of Callosal Projection Neurons in the Mouse Medial Prefrontal Cortex - Stephens, Emily K.; Baker, Arielle L.; Gulledge, Allan T. (Frontiers in Neural Circuits, 2018)
Serotonin (5-HT) selectively excites subpopulations of pyramidal neurons in the neocortex via activation of 5-HT2A (2A) receptors coupled to Gq subtype G-protein alpha subunits. Gq-mediated excitatory responses have been attributed primarily to suppression of potassium conductances, including those mediated by KV7 potassium channels (i.e., the M-current), or activation of nonspecific cation conductances that underly calcium-dependent afterdepolarizations (ADPs). However, 2A-dependent excitation of cortical neurons has not been extensively studied, and no consensus exists regarding the underlying ionic effector(s) involved. In layer 5 of the mouse medial prefrontal cortex, we tested potential mechanisms of serotonergic excitation in commissural/callosal (COM) projection neurons, a subpopulation of pyramidal neurons that exhibits 2A-dependent excitation in response to 5-HT. In baseline conditions, 5-HT enhanced the rate of action potential generation in COM neurons experiencing suprathreshold somatic current injection. This serotonergic excitation was occluded by activation of muscarinic acetylcholine (ACh) receptors, confirming that 5-HT acts via the same Gq-signaling cascades engaged by ACh. Like ACh, 5-HT promoted the generation of calcium-dependent ADPs following spike trains. However, calcium was not necessary for serotonergic excitation, as responses to 5-HT were enhanced (by >100%), rather than reduced, by chelation of intracellular calcium with 10 mM BAPTA. This suggests intracellular calcium negatively regulates additional ionic conductances gated by 2A receptors. Removal of extracellular calcium had no effect when intracellular calcium signaling was intact, but suppressed 5-HT response amplitudes, by about 50% when BAPTA was included in patch pipettes. This suggests that 2A excitation involves activation of a nonspecific cation conductance that is both calcium-sensitive and calcium-permeable. M-current suppression was found to be a third ionic effector, as blockade of KV7 channels with XE991 (10 µM) reduced serotonergic excitation by ~50% in control conditions, and by ~30% with intracellular BAPTA present. These findings demonstrate a role for at least three distinct ionic effectors, including KV7 channels, a calcium-sensitive and calcium-permeable nonspecific cation conductance, and the calcium-dependent ADP conductance, in mediating serotonergic excitation of COM neurons.